Innovation in Vocational Learning: Project Based Learning E-Module on the Textile Dyeing Course - Pratiwi, Mala Maulidina; Waskito; Nelmira, Weni; Ambiyar (Universitas Pendidikan Ganesha, 2024)
The current problem is the lack of innovative learning resources that can be used for independent learning. This has an impact on low student learning outcomes. The aim of this research is to develop an E-module based on Project Based Learning. This type of research is development research.The model used to develop products is 4-D (definition, design, development and distribution). The research subjects were 2 material expert validators, 3 media expert validators, and 2 language expert validators. The product trial subjects were 16 students who were taken into two classes as a control class and an experimental class. The methods used to collect data are observation, interviews, questionnaires and tests. The instruments used to collect data were questionnaire sheets and test questions. This research data analysis technique uses descriptive qualitative, quantitative and inferential statistical analysis. The research results areThe average material validation assessment was 0.86 with the Valid category. The average result of the E-module validation assessment in terms of media is 0.85 with the Valid category. The language validation assessment was 0.86 in the valid category. Practicality by lecturers was 91.67% in the very practical category and students were 82.5% in the very practical category. This e-Module was declared effective in improving student learning outcomes based on classical completeness of 94.73%, and a score of 0.71 in the high category. It was concluded that E-modules are suitable for use in learning and can improve student learning outcomes.